Inequality is Not the Problem. What Matters is Relational Trouble. - Waldzus, S.; Bernardes, S.F.; Guerra, R.; Stathi, S. (17th Jena Workshop and EASP medium size meeting on ‘Social Justice: Inequality and Recognition, 2015)
We will present the hypothesis that inequality as such is not a problem in intergroup relations but that it appears problematic when it implies lack of relational complementarity. Our theoretical approach, which departs from Alan Fiske’s relational models theory, assumes that one fundamental social motive, the need for relational complementarity, can explain parsimoniously a wide range of people’s social behavior, including intergroup behavior that traditional approaches explain as responses to injustice. The hypothesis will be backed up with three types of research results. We will present a) a line of research showing that relational complementarity fulfills people’s needs for belonging, trust and control and increases cooperative behavior b) a study with 224 black and white children showing that the most relational variable, namely meta-perceptions, is the strongest predictor of actual intergroup behavior – stronger than other socio-cognitive and emotional measures, and c) an international study conducted in Greece, Italy and Portugal showing that in all three countries people perceive discrepancies between actual and ideal relations between countries within the European Union and that some of these discrepancies predict readiness to support or engage in non-normative (e.g., violent) action.